Multifunctional Geometric Metasurfaces Based on Tri‐Spectral Meta‐Atoms with Completely Independent Phase Modulations at Three Wavelengths. Issue 9 (13th August 2020) - Xie, Rensheng; Zhai, Guohua; Gao, Jianjun; Zhang, Dajun; Wang, Xiong; An, Sensong; Zheng, Bowen; Zhang, Hualiang; Ding, Jun
Abstract: Metasurface has drawn much attention due to its unprecedented wave‐front manipulation abilities with an ultrathin flat profile. However, the metasurface as a diffractive device usually suffers from chromatic aberrations, which greatly hinders the design freedom at different wavelengths. In this work, it is demonstrated that this limitation can be overcome by a multifunctional metasurface with completely independent phase modulations at three arbitrarily wavelengths. Specifically, a novel single‐layer tri‐spectral meta‐atom composed of three alternatively arranged slot and metallic resonators is proposed to operate at three distinct wavelengths, where 2π geometric phase modulations under the circularly polarized incidence can be achieved independently by rotating the corresponding resonators. As proof of concept demonstrations, a tri‐wavelength vortex beam generator and a meta‐hologram are designed to verify the proposed method. First, a vortex beam generator with arbitrary topological charge numbers at three wavelengths is designed and verified through theoretical calculation and full‐wave simulation. Moreover, a meta‐hologram generated by the computer‐generated holography is designed to display three frequency selective holographic images on the same image plane. The tri‐wavelength meta‐hologram is validated through theoretical calculation, full‐wave simulation, and experiment. The experimental results agree very well with the numerical ones, demonstrating the attractive capabilities of multifunctionalities at three wavelengths. Abstract : The tri‐spectral multi‐functional meta‐device produces vortex beam, focusing beam and holographic image 'N' at three preset frequencies of f1, f2 and f3, respectively.